The effect of injury definition and surveillance methodology on measures of injury occurrence and burden in elite volleyball - MacDonald, K. J.; Palacios-Derflingher, L. M.; Emery, C. A.; Meeuwisse, W. H. (International Journal of Sports Medicine, 2017)
A time-loss injury definition continues to be the most widely used injury definition despite evidence that it fails to accurately capture overuse injuries. An overuse injury questionnaire, using an "all complaints" definition has been created to address the limitation of a time-loss definition. The main aim of this work was to determine the effect that injury definition and registration methodology has on the collection of knee injuries among elite level volleyball players. To reach this goal, seventy-two volleyball players were prospectively followed over 32-weeks. Time-loss injuries were captured using an individual injury report form (IIRF). Study participants completed an overuse injury questionnaire (mOIQ) via a weekly short message service (SMS). The IIRF captured 15 time-loss knee injuries in 72 study participants (20%). Based on the mOIQ, 84.7% of participants reported having a knee problem and 66.7% sustained a substantial knee problem. All IIRF knee injuries captured were also registered by the mOIQ. Agreement on the specific diagnosis occurred for 66.7% of injuries resulting in a moderate Kappa score of 0.51. In conclusion, an overuse injury questionnaire provided a greater understanding of the magnitude and burden of knee injuries in this population.